Decision Support System For Approval New Student And Majoring Selection Based On Student’s Interest And Talent By Fuzzy Multiple Decision Making, Simple Additive Weighting And Buble Sort Method In SMK Telekomunikasi Tunas Harapan - Dewi Nurdiyah (Jurnal Transformatika, 2016)
Decision Support System for New Student Acceptance aims to simplify the Decision Maker who is the Committee of New Student Acceptance to select prospective new students based on eight criteria. That is registration number, the average value of National Examinations, medical tests, interview, their achievements, salary of parents per month, number of siblings who are still in school and administration department and give recommendations for the major of accepted students based on their interests and talents. There are four major in SMK Telekomunikasi Tunas Harapan, these are Rekayasa Perangkat Lunak (RPL), Teknik Komputer dan Jaringan (TKJ), Multimedia and Teknik Kendaraan Ringan (TKR). And the talents be measured by math test, electro test, daw test and physics test.